Making good citizens : education and civil society - Ravitch, Diane; Viteritti, Joseph P., 1946- (New Haven : Yale University Press, 2001)
Americans have reason to be concerned about the condition of American democracy at the start of the twenty-first century. Surveys show that civic participation has declined, cynicism about government has increased, and young people have a weak grasp of the principles that underlie our constitutional system. Crucial questions must be answered: How serious is the situation? What role do schools play in shaping civic behaviour? Are current education reform initiatives, such as multiculturalism and school choice, counterproductive? How can schools contribute toward reversing the trend? This volume brings together leading thinkers from a variety of disciplines to probe the relation between a healthy democracy and education. Their original and provocative discussions cut across a range of important topics: the cultivation of democratic values, the formation of social capital in schools and communities, political conflict in a pluralist society, the place of religion in public life, the enduring problems of racial inequality. Gathering together the most recent research and thinking on education and civil society, this is a book that deserves the attention of everyone who cares about the quality and future of American democracy.
Introduction / Diane Ravitch & Joseph P. Viteritti -- Education and democracy / Diane Ravitch -- Education and democratic citizenship / Norman Nie & D. Sunshine Hillygus -- Community-based social capital and educational performance / Robert D. Putnam -- Fluctuations of social capital in an urban neighborhood / Gerald Grant -- To not fade away : restoring civil identity among the young / William Damon -- Moral disagreement, moral education, common ground / Warren A. Nord -- Some problems in acknowledging diversity / Nathan Glazer -- Education and citizenship in an age of pluralism / Mark Holmes -- Common education and the democratic ideal / Rosemary C. Salomone -- Once more into the breach : reflections on Jefferson, Madison, and the religion problem / Jack N. Rakove -- Civil society, religion, and the formation of citizens / Jean Bethke Elshtain -- Schooling and religious pluralism / Alan Wolfe -- Religion and education : American exceptionalism? / Charles L. Glenn -- Risking choice, redressing inequality / Joseph P. Viteritti.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Citizenship -- Study and teaching -- United States; Civics -- Study and teaching -- United States; Education -- Aims and objectives -- United States; Éducation à la citoyenneté -- États-Unis.; Éducation -- Finalités -- États-Unis.; Citoyenneté -- Étude et enseignement -- États-Unis.; EDUCATION -- Aims & Objectives; EDUCATION -- Philosophy & Social Aspects; Citizenship -- Study and teaching; Civics -- Study and teaching; Education -- Aims and objectives; United States; Onderwijs; Doelstellingen; Burgerschap; Democratie; Politieke socialisatie